1975
DOI: 10.1159/000178681
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Induced Tetany in Idiopathic Hypoparathyroidism

Abstract: A 35-year-old woman experienced tetanic symptoms when treated with chorionic gonadotrophins or estrogenic oral contraceptives. Persistent hypocalcemia was found, with hyperphosphatemia, normal renal function and low normal plasma parathyroid hormone (PTH), all consistent with idiopathic hypoparathyroidism. During EDTA infusion, no PTH response was measured with a predominantly anti-NH2 -terminal antiserum, but a normal response was found with a predominantly anti-COOH-terminal antiserum. This supposes secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Since then, oestrogens have been widely used in the treatment of osteoporosis. Oestrogens inhibit bone resorption induced by parathyroid hormone (PTH) in vivo (Orimo et al, 1972: Gallagher & Wilkinson, 1973 and in vitro (Atkins et al, 1972) and lower serum calcium levels (Young et al, 1968;Aitken et al, 1971;Riggs el al., 1972;Burckhardt et al, 1975;Goulding & McChesney, 1977). The antagonism of oestrogens to Correspondence: Dr S. Morimoto.…”
mentioning
confidence: 99%
“…Since then, oestrogens have been widely used in the treatment of osteoporosis. Oestrogens inhibit bone resorption induced by parathyroid hormone (PTH) in vivo (Orimo et al, 1972: Gallagher & Wilkinson, 1973 and in vitro (Atkins et al, 1972) and lower serum calcium levels (Young et al, 1968;Aitken et al, 1971;Riggs el al., 1972;Burckhardt et al, 1975;Goulding & McChesney, 1977). The antagonism of oestrogens to Correspondence: Dr S. Morimoto.…”
mentioning
confidence: 99%
“…However, the PTH results obtained in the third patient with discrepant basal PTH levels, who had tetanv of unknown origin, are consistent with the syndrome described by Nusino¬ witz & Klein (1973). Discrepant PTH responses to EDTA have also been observed in a second patient and have already been published (Burckhardt et al 1975). However, basal PTH levels were normal despite marked hypocalcaemia which led again to the diagnosis of idiopathic hypoparathyroidism.…”
Section: )mentioning
confidence: 60%
“…A subset of the patients complained of hypocalcemic symptoms in the perimenstrual phase. Though several investigators have reported similar clinical observation [14-18], there is only one systematic study and an isolated case report investigating relationship of serum calcium with menstruation in patients with hypoparathyroidism [19,20] and the results were variable. It was also suggested that hypocalcemic symptoms during perimenstrual phase might be a reflection of PMS rather than hypocalcemia [19].…”
Section: Introductionmentioning
confidence: 99%